Direct and Indirect Compliment Responses: A Descriptive Qualitative Study among Indonesians and Americans - wulansari wulansari (Celt: A Journal of Culture, English Language Teaching & Literature, 2020)
Abstract: Indonesians and Americans have the strategies to respond the compliment which came from different culture. The aims of this research were addressing types of strategies and disclosing the direct and indirect response used by the Indonesians and Americans to respond the compliments. The research data consist of English and Indonesian. The data was analyzed by using qualitative method. The Discourse Completion Test (DCT) questionnaire was used to know the differences between compliment response given to Indonesians and Americans. The result of the research showed that the (1) responded category of Holmes (1986) classification of compliment responses strategies (CRs) are using three strategies (accept, reject and evade) among Indonesians and Americans. Indonesians tended to accept, reject and evade compliment by giving some reasons. While Americans tended using three categories by saying, "thank you" due to express of openness and receiving appreciation from the interlocutor. (2) The existence of culture plays an important role in responding compliment towards Indonesians and Americans. The Americans respond to compliments direct response and simple answers to compliments. Meanwhile, Indonesians prefer to respond compliment with indirect responses because they were leaning on the principle known as saving face politeness.